2020
DOI: 10.1371/journal.pone.0227855
|View full text |Cite
|
Sign up to set email alerts
|

Tks5 SH3 domains exhibit differential effects on invadopodia development

Abstract: The Src substrate Tks5 helps scaffold matrix-remodeling invadopodia in invasive cancer cells. Focus was directed here on how the five SH3 domains of Tks5 impact that activity. Mutations designed to inhibit protein-protein interactions were created in the individual SH3 domains of Tks5, and the constructs were introduced into the LNCaP prostate carcinoma cell line, a model system with intrinsically low Tks5 expression and which our lab had previously showed the dependence of Src-dependent Tks5 phosphorylation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Both TKS4 and TKS5 have a cytoplasmic, inactive state, and a membrane-bound, active state in cells. The transition between these states is most likely regulated by phosphorylation [2,10,11]. Direct evidence for these conformational states is still limited [12].…”
Section: The Regulated Localization Of Tks Proteins Determines Their Signal Recruiting Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both TKS4 and TKS5 have a cytoplasmic, inactive state, and a membrane-bound, active state in cells. The transition between these states is most likely regulated by phosphorylation [2,10,11]. Direct evidence for these conformational states is still limited [12].…”
Section: The Regulated Localization Of Tks Proteins Determines Their Signal Recruiting Functionmentioning
confidence: 99%
“…They also showed that, when constitutively active SRC is present, TKS4 accumulates in podosomes (actin-rich membrane protrusions involved in cell motility, see below) while forming a complex with SRC and cortactin [9]. TKS5 has also been reported to bind cortactin and other proteins important in the regulation of actin cytoskeleton assembly, including N-WASP, non-catalytic region of tyrosine kinase adaptor protein (NCK), and GRB2 (for a full list, see Table 1b) [10,29,52,78,79].…”
Section: Unknownmentioning
confidence: 99%
“…5, G and H ). This bundling phenotype caused by the 2RA mutation was not canceled by an additional mutation in each C-terminal SH3 domain, W470A, W862A, or W1093A, which abolished their binding to proline-rich motif-containing proteins ( Rufer et al, 2009 ; Daly et al, 2020 ), or triple mutations, W470A/W862A/W1093A (3WA; Fig. 5, G and H ; and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The SH3PXD2A gene was expressed at higher levels in breast, colon, lung and prostate cancer tissues than in normal tissues [29]. The dysregulation of SH3PXD2A gene expression has been shown in many diverse cancers [30][31][32][33], and lncRNA generation in the SH3PXD2A genes may play important roles in tumorigenesis. We showed that increased SH3PXD2A-AS1 expression was associated with a poor prognosis and shorter survival time in NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%